2017
DOI: 10.3389/fpsyg.2017.00085
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Avoidance Is Significantly Related to Attentional Preference for Infant Faces: Evidence from Eye Movement Data

Abstract: Objective: To determine the influence of adult attachment orientations on infant preference.Methods: We adopted eye-tracking technology to monitor childless college women’s eye movements when looking at pairs of faces, including one adult face (man or woman) and one infant face, with three different expressions (happy, sadness, and neutral). The participants (N = 150; 84% Han ethnicity) were aged 18–29 years (M = 19.22, SD = 1.72). A random intercepts multilevel linear regression analysis was used to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 69 publications
(83 reference statements)
3
23
0
Order By: Relevance
“…Third, a finding distinct from the above studies regarding the emotional valence of expressions is that the effect sizes of the babyface schema for neutral faces were significantly greater than those for happy or sad faces on the preference response and the viewing motivation along with those for sad faces on the attention bias. These results are consistent with those of previous studies (Ding et al, 2016;Jia et al, 2017), showing an inverted V-shaped trend. For the first time, these findings demonstrated the phenomenon of the strongest effect of the neutral babyface schema as determined through rigorous comparisons with adult faces used as a baseline and multiple matched expressions on the same faces.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Third, a finding distinct from the above studies regarding the emotional valence of expressions is that the effect sizes of the babyface schema for neutral faces were significantly greater than those for happy or sad faces on the preference response and the viewing motivation along with those for sad faces on the attention bias. These results are consistent with those of previous studies (Ding et al, 2016;Jia et al, 2017), showing an inverted V-shaped trend. For the first time, these findings demonstrated the phenomenon of the strongest effect of the neutral babyface schema as determined through rigorous comparisons with adult faces used as a baseline and multiple matched expressions on the same faces.…”
Section: Discussionsupporting
confidence: 94%
“…Second, a stronger viewing motivation is induced in adults by infant faces than by adult faces, which is represented as approach propensity and view tendency (Cheng et al, 2015; Ding et al, 2016; Hahn et al, 2013; Parsons, Young, Kumari, et al, 2011). Third, adults show a stronger obvious attention bias towards infant faces than adult faces (Brosch et al, 2007; Charles et al, 2013; Jia et al, 2017; Thompson-Booth et al, 2014). These studies indicate that an infant face is an effective stimulus that can induce a parenting response and is an important cue for the formation of human parenting behaviour and early parent–child relationships (Franklin & Volk, 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, our results were more consistent with studies using eye-tracking methods in that we found no effect of attachment avoidance on oculomotor attention to emotional faces (Byrow, Broeren, et al, 2016; Jia et al, 2017; Vandevivere et al, 2014; Vrticka et al, 2008). One key difference, however, was that Vandevivere et al (2014) found an effect of attachment avoidance on attentional bias for an attachment figure’s face, which we did not replicate.…”
Section: Resultssupporting
confidence: 92%
“…However, across studies that have found emotion-specific effects of attachment avoidance, the nature of this emotion-specific effect has been inconsistent: Studies have found reduced attentional bias to both positive and negative expressions (Byrow, Chen, & Peters, 2016;Dewitte & De Houwer, 2008), reduced neural processing of positive, but not negative, expressions (Vrtička et al, 2012) or reduced attention to negative, but not positive, expressions (Dewitte, 2011;Suslow et al, 2009Suslow et al, , 2010. Further, effects of attachment avoidance on attention to emotional faces have failed to replicate in a considerable number of studies (Byrow, Broeren, et al, 2016;Cooper et al, 2009;Davis et al, 2014;Fraley et al, 2006;Jia et al, 2017;Meinz et al, 2017;Vandevivere et al, 2014;Vrticka et al, 2008;Westphal, 2014;Zhang et al, 2008). Consequently, it is still unclear whether attachment avoidance reliably influences visual attention to emotional facial expressions.…”
Section: Attachment Avoidance and Attention To Emotional Facesmentioning
confidence: 99%